A LINGUISTIC STUDY OF GENERAL NOUNS IN ENGLISH AND VIETNAMESE - Mai Thị Thúy Diễm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study aims at finding out the cohesive and semantic features of general nouns in English and Vietnamese for the purpose of implication in teaching and learning English. The data for the study are collected from websites, stories and novels. The study is carried out through the adoption of descriptive, analytic, qualitative and contrastive approaches. In the finding and discussion, in terms of cohesive features of general nouns, we have focused on discussing grammatical and lexical cohesiveness of general nouns and their subordinate members in both languages mainly in view of Halliday and Hasan [12] and John Flowerdew [16]. With respect to semantic features of general nouns, the class of general nouns is a small set of nouns having generalized reference within the major noun class are analyzed and argued. Simultaneously, the similarities and the differences between English and Vietnamese general nouns in terms of cohesive as well as semantic features are also emphasized. It is hoped that the findings of the research will make a certain contribute to teaching and learning discourse analysis in general and general nouns in particular.